Health‐related quality of life, obesity, fragmented sleep, fatigue, and psychosocial problems among youth with craniopharyngioma. Issue 5 (2nd December 2021) - Klages, Kimberly L.; Berlin, Kristoffer S.; Cook, Jessica L.; Merchant, Thomas E.; Wise, Merrill S.; Mandrell, Belinda N.; Conklin, Heather M.; Crabtree, Valerie McLaughlin
Abstract: Objective: Youth with craniopharyngioma experience weight gain, fragmented sleep, excessive daytime sleepiness (EDS), fatigue, and psychosocial problems that negatively impact their overall health‐related quality of life (HRQoL). Greater hypothalamic tumor involvement (HI) may be associated with higher rates or severity of these impairments; however, the direct and indirect impact of HI on the physical and psychosocial consequences associated with pediatric craniopharyngioma remain unclear. The purpose of the current study was to examine relations between HI, body mass index (BMI), fragmented sleep, EDS, fatigue, psychosocial problems, and HRQoL among youth with craniopharyngioma. Methods: Eighty‐four youth with craniopharyngioma ( M age = 10.27 ± 4.3 years, 53.6% female, 64.3% White) were assessed with actigraphy, nocturnal polysomnography, and multiple sleep latency tests prior to proton therapy, when indicated. Caregivers completed measures of fatigue, psychosocial functioning, and HRQoL. Results: Hypothalamic tumor involvement was associated with greater BMI ( Est . = 2.97, p = 0.003) and daytime sleepiness ( Est . = 2.53, p = 0.01). Greater fatigue predicted more psychosocial problems ( Est . = 0.29, p < 0.001) and lower HRQoL ( Est . = 0.23, p = 0.001). Psychosocial problems also predicted lower HRQoL ( Est . = −0.34, p = 0.004). Fragmented sleep ( Est . = 0.03, p = 0.04) and fatigue ( Est . = 0.10, p = 0.02) indirectly predicted lower HRQoL through psychosocial problems. Conclusions: Youth with craniopharyngioma with greater HI may benefit from weight reduction interventions and management of excessive sleepiness. Patients should be prospectively monitored for sleep problems, fatigue, and psychosocial problems, as these patients may benefit from interventions targeting fatigue and psychosocial health to improve HRQoL.